Multimedia databases and image communication: Proceedings of the workshop on Mdic 2004, Salerno, Italy 22 June 2004 - Abate, Andrea F; Nappi, Michele; Sebillo, Monica (Series on software engineering and knowledge engineering, 2004)
There is a strong need for advances in the fields of image indexing and retrieval and visual query languages for multimedia databases. Image technology is facing both classical and novel problems for the organization and filtering of increasingly large amounts of pictorial data. Novel kinds of problems, such as indexing and high-level content-base, accessing to image databases, human interaction with multimedia systems, approaches to multimedial data, biometrics, data mining, computer graphics and augmented reality, have grown into real-life issues.